Evaluation of dietary intake of calcium in adult subjects with idiopathic arterial hypertension - Waib, P. H. [UNESP]; Papini-Berto, S. J.; Habermann, F.; Burini, R. C. (Revista De Saúde Pública, 1992)
The calcium-intake relationship with other alimentary and anthropometric variables was investigates in a group of 60 adult (19-75 year-old) subjects, 50 females and 10 males, with essential arterial hypertension (DAP > 90 mmHg). The calcium intake was assessed by three different protocols: 24-hour food intake recall, food-frequency questionnaire and 3 day self-food intake register, repeated along with anthropometric measurements on three different occasions (2-15 month-intervals). The calcium intake assessed by the three methods, as well as the anthropometric data, were statistically similar on all three occasions. The mean data were then compared with those form the control, composed of 75 healthy subjects matched with the hypertensive group by age and sex. The patients ingested less calcium (mean +/- SD) than the controls on the daily (517 +/- 271 x 740 +/- 353 mg/d) and body-weight (8.1 +/- 5.0 x 11.4 +/- 5.9 mg/kg/d) basis. Among the males the calcium intake was the only difference found between groups and could be attributed to the lower intake of calcium-rich foods. The hypertensive females showed also higher lean-body mass (Body-mass index and arm muscle circumference). Thus the calcium intake discriminated both groups being associated with changes in other nutritional parameters only in females.